(untitled) (Third Sector Social Economic Review, 2022)
In this study, the convergence characteristics of the inflation rates of 15 countries that were members until the Fourth Enlargement phase of the EU in the 1993M1-2021M12 period are examined. Considering the period and country group in question, the aim of the study is to determine the effect of the Maastricht agreement on the inflation rates of the countries that were members of the EU through the with convergence hypothesis. The convergence hypothesis was tested using the Nahar-Inder technique, which detects the presence of convergence even if the series is not stationary and can show intra-sample mobility. According to the findings, while inflation rates convergence in 12 out of 15 countries, inflation rates divergence in the Netherlands, Luxembourg and Sweden. The negative effects created by the ""Dutch Disease"" for the Dutch economy are still continuing, and therefore the reason for the divergence in inflation rates is shown. The strong ties of Luxembourg, a Benelux country, with the Dutch economy causes divergence behavior. For the Swedish economy, inflation rates diverge due to the existence of a strong union structure, the economic crisis in the 1990s and the high inflation period created by it. In this context, the European Central Bank should monitor the convergence behavior of inflation rates and take it into account in its decision processes. In this direction, both traditional and non-traditional monetary policies should be implemented to rein in inflation rates, and the continuity of economic efficiency should be ensured by implementing fiscal policies that support monetary policies.